Growth, Blood Chemistry and Carcass Yield of Broilers Fed Cassava Leaf Meal (Manihot esculenta Crantz) - Iheukwumere, F.C.; Ndubuisi, E.C.; Mazi, E.A.; Onyekwere, M.U. (International Journal of Poultry Science, 2007)
A 25-day feeding trial involving 120, 5-week old Anak broilers was carried out in a completely randomized design to evaluate, growth, blood chemistry and carcass yield of broilers fed cassava leaf meal at dietary levels of 0, 5, 10 and 15% respectively. Feed intake, body weight gain, feed conversion ratio and the control (0%) leaf meal were superior (p0.05) between the treatment group. The cut parts of the carcass showed superior values (p